Crystal structure of AdoMet radical enzyme 7‐carboxy‐7‐deazaguanine synthase from Escherichia coli suggests how modifications near [4Fe–4S] cluster engender flavodoxin specificity. (17th December 2018) - Grell, Tsehai A.J.; Bell, Benjamin N.; Nguyen, Chi; Dowling, Daniel P.; Bruender, Nathan A.; Bandarian, Vahe; Drennan, Catherine L.
Abstract: 7‐Carboxy‐7‐deazaguanine synthase, QueE, catalyzes the radical mediated ring contraction of 6‐carboxy‐5, 6, 7, 8‐tetrahydropterin, forming the characteristic pyrrolopyrimidine core of all 7‐deazaguanine natural products. QueE is a member of the S ‐adenosyl‐L‐methionine (AdoMet) radical enzyme superfamily, which harnesses the reactivity of radical intermediates to perform challenging chemical reactions. Members of the AdoMet radical enzyme superfamily utilize a canonical binding motif, a CX3 CXϕC motif, to bind a [4Fe‐4S] cluster, and a partial (β/α)6 TIM barrel fold for the arrangement of AdoMet and substrates for catalysis. Although variations to both the cluster‐binding motif and the core fold have been observed, visualization of drastic variations in the structure of QueE from Burkholderia multivorans called into question whether a re‐haul of the defining characteristics of this superfamily was in order. Surprisingly, the structure of QueE from Bacillus subtilis revealed an architecture more reminiscent of the classical AdoMet radical enzyme. With these two QueE structures revealing varying degrees of alterations to the classical AdoMet fold, a new question arises: what is the purpose of these alterations? Here, we present the structure of a third QueE enzyme from Escherichia coli, which establishes the middle range of the spectrum of variation observed in these homologs. With these three homologs, we compare and contrast the structural architecture and make hypotheses about the role of these structural variations in binding and recognizing the biological reductant, flavodoxin. Broader impact statement: We know more about how enzymes are tailored for catalytic activity than about how enzymes are tailored to react with a physiological reductant. Here, we consider structural differences between three 7‐carboxy‐7‐deazaguanine synthases and how these differences may be related to the interaction between these enzymes and their biological reductant, flavodoxin. Abstract : PDB Code(s):4NJI, 4NJG, 5TH5, 1AHN